Rehabilitation Policy for Drugs Abuse in Indonesia - Yusuf Saefudin1, Hartiwiningsih2 , Isharyanto3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Narcotics Abuse and Distribution are the main causes of the continuing number of narcotics addicts inIndonesia. Therefore, the Indonesian government has formulated a policy to deal with narcotics crimes,which will allow the handling of narcotics addicts and non-narcotics addicts. This article discusses therehabilitation policy for narcotics addicts in Indonesia. This research is a normative juridical research.Designed using the statute approach and conceptual approach. The results of the research show that: first,the issue and distribution of narcotics are narcotics crimes; Second, Indonesia makes a policy regarding thehandling of narcotics addicts and non-narcotics addicts; Third, the means to determine someone in narcoticsor not is done through an assessment that is governed by an assessment made through a Joint Regulation ofthe relevant state institution.